Multidisciplinary Assessment and Management of Nasal Septal Fracture Across Nursing, Dentistry, Pharmacy, Laboratory, and Emergency Care-An Updated Review - Al-Hafizi, Maryam Saleh; Hasnah Mohammed Alessa; Muhammed Abdulkareem Alhazoom; Amnah Ahmed Alhuwayji; Yasir Mohammed Faleh Alsharari; Wedad Magani Sherwani; Abdullah Saleh Alaoffey; Mohameed Hamoud Alqayd; Mousa Hamoud Alqayd; Ashwag Owid Alenezi (Saudi Journal of Medicine and Public Health, 2025)
Background: Nasal septal and nasal bone fractures represent the most common injuries within maxillofacial trauma due to the exposed anatomical position of the nasal framework and its limited structural resistance to external forces. These injuries frequently coexist with other facial fractures and may result in both functional airway compromise and aesthetic deformity. Given the anatomical complexity and clinical variability, their management requires a multidisciplinary approach. Aim: This review aims to provide an updated and comprehensive synthesis of nasal septal fracture management, emphasizing multidisciplinary involvement across nursing, dentistry, pharmacy, laboratory medicine, and emergency care. It also highlights current evidence regarding diagnosis, imaging, treatment strategies, complications, and preventive measures. Methods: A narrative review approach was adopted based on previously published literature and clinical studies addressing nasal fracture epidemiology, pathophysiology, diagnostic evaluation, and management principles. Emphasis was placed on integrating clinical guidelines and multidisciplinary healthcare perspectives relevant to trauma care pathways. Results: Findings indicate that nasal fractures are predominantly caused by interpersonal violence, motor vehicle accidents, sports trauma, and falls, with demographic variation by age and sex. Clinical assessment remains central to diagnosis, while CT imaging is reserved for complex cases. Management ranges from conservative observation to closed reduction and delayed reconstructive surgery. Septal hematoma, septal perforation, and saddle nose deformity remain key complications. Early intervention improves outcomes, while delayed treatment increases the likelihood of deformity and revision surgery. Multidisciplinary collaboration improves detection, treatment accuracy, and long-term functional and cosmetic results. Conclusion: Nasal septal fractures require early recognition and structured multidisciplinary management to optimize outcomes. Integration of emergency care, surgical specialties, and allied health services is essential to reduce complications and improve patient recovery.